Science links 8 : worktext for scientific and technological literacy - Madriaga, Estrellita A. Ph.D.; Valdoz, Meliza P.; Aquino, Marites D.; Castillo, Mary Anne B. (Sampaloc Manila Rex Book Store, Inc., 2017)
"This book is a program that provides an interdisciplinary approach such as the social, historical, philosophical, technological, and problem-solving contexts in the teaching learning process." This series, Science Links 8 new edition, aims to acquaint the students with the physical sciences that will help them understand and explain natural phenomena and increase their awareness of the role of human beings in preserving, conserving, and protecting the environment. Each worktext in this series has four quarters, each quarter is introduced by by an illustration and background information to direct the students' focus on the subject matter. It is also divided into units, and each unit has an unit title page that provides the students with key questions and an overview of the concepts. The unit ends with a differentiated summative assessment task and a unit test.
Includes glossary, bibliography, index
English text